THE INFLUENCE OF JOB SATISFACTION AND WORK DISCIPLINE ON WORK MOTIVATION IN BAPPEDA EMPLOYEES OF JAMBI CITY - Kartika, Yulia Dwi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
This study examines how job satisfaction and work ethic affect employees of Jambi City Bappeda's motivation to work hard. Using saturated sampling or a census as the sampling method, this study used a quantitative approach with a sample size of 70 participants. Using SPSS software version 25, several linear regression analysis approaches were used to the research data. The findings indicated that the variables of job satisfaction and work discipline both partially and simultaneously had a positive and substantial effect on work motivation, with job satisfaction serving as the most important independent variable in this relationship.